Pengaruh Penggunaan Katalis (Zeolit) Terhadap Kinetic Rate Tar Hasil Pirolisis Serbuk Kayu Mahoni (Switenia Macrophylla) - Kumara, Dody Candra; Wijayanti, Widya; Widhiyanuriyawan, Denny (Jurnal Rekayasa Mesin, 2015)
This research was conducted to find out the influence of the use of a catalyst (zeolite) against kinetic rate results of tar pyrolysis of sawdust mahogany. research process undertaken experimentally with temperature 523K and 873K on the heating rate 673 K/hour. pyrolysis is done for 3 hours with wood powder particle size 0,5 â€“ 1 mm. before use activated zeolite in advance by means of heated at a temperature of 400 Â°c for 1 hour. the results showed the value of kinetic rate tar with zeolites greater than without zeolites , where the value of the kinetic rate equation obtained i.e. ð‘˜ = 185,49. ð‘’ âˆ’2779/ð‘‡ (heating rate 673 K/hour without zeolite) and ð‘˜ = 93,037. ð‘’ (heating rate 673 K/hour with zeolite). The results of the validation shows the value addition in the calculation of the volume is already approaching the actual value.